2010
DOI: 10.1111/j.1526-4610.2010.01777.x
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Intimate Partner Violence, Migraine and Probable Migraine

Abstract: Objective Intimate partner violence (IPV) among women is a global public health problem. The association between childhood maltreatment and migraine is well established, but not the association between IPV and migraine. The aim of this cross-sectional study was to evaluate the relationship between type and severity of IPV and migraine in a large cohort of Peruvian women. Methods Women who delivered singleton infants (N=2,066) at the Instituto Nacional Materno Perinatal, Lima, Peru were interviewed during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 74 publications
1
35
1
2
Order By: Relevance
“…20 The short-and long-term consequences of adverse childhood experiences, including abuse and neglect, can result in a multitude of physical and social problems. 22 Headaches, [23][24][25][26][27][28] fibromyalgia, chronic pain syndromes, syncope, and psychogenic nonepileptic seizure have been linked to abuse. 29 -32 In addition, adults who were exposed to parental verbal abuse experienced higher rates of depression, irritability, and somatization.…”
Section: Abuse and Its Relationship To Neuro-mentioning
confidence: 99%
“…20 The short-and long-term consequences of adverse childhood experiences, including abuse and neglect, can result in a multitude of physical and social problems. 22 Headaches, [23][24][25][26][27][28] fibromyalgia, chronic pain syndromes, syncope, and psychogenic nonepileptic seizure have been linked to abuse. 29 -32 In addition, adults who were exposed to parental verbal abuse experienced higher rates of depression, irritability, and somatization.…”
Section: Abuse and Its Relationship To Neuro-mentioning
confidence: 99%
“…However, that study did not use standardized measures of abuse, making the results difficult to generalize. A recent study of post-partum hospitalized women in Peru found that 34.8% of migraine sufferers reported a lifetime history of IPV (Cripe et al, 2011). Neither of these studies ascertained recent or 12-month prevalence rates of IPV in the populations studied.…”
Section: Introductionmentioning
confidence: 97%
“…Abused women have 1.5 to 2 times higher risk of chronic pain, including headache (Coker et al, 2002) (see Figure 1). Women who are victims of IPV are up to 60% more likely to suffer from headache than unabused controls (Coker et al, 2002;Cripe et al, 2011). A retrospective chart review of mostly female (90.1%) tertiary care headache patients in the United States found that nearly 35% reported a lifetime history of physical and/or sexual abuse (Peterlin et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Existe evidencia de las graves consecuencias, directas e indirectas, que ocasiona la violencia de pareja en la salud de la mujer (2)(3)(4)(5) . La prevalencia de violencia física o sexual contra la mujer por la pareja es alta aunque puede variar según los ámbitos geográficos.…”
Section: Introductionunclassified
“…Prevalence of physical violence at the national level was 14,5%, with variations according to the geographical areas (9,7% to 18,9%). The factor associated to a higher risk is having a couple who frequently gets drunk (OR: 7,2; 95%CI: 5,4-9,6) and having a couple controlling or limiting the woman's visits to family or friends (OR: 4,1; 95%CI: 3,(3)(4)(5)0); other associated factors are history of physical aggression of the father to the mother, having had previous partners, be cohabiting, having a higher educational level than the partner and having a disbalanced decision taking in the couple. Among the factors associated with a lower risk are the communication and respect inside the couple (OR: 0,3; 95%CI: 0,2-0,3), and the fact that the woman has health insurance.…”
mentioning
confidence: 99%